Special and differential treatment in the WTO: Why, when and how? - Alexander Keck; Patrick Low (World Trade Organization (WTO), 2004)
This paper analyses to which extent domestic institutions affect trade flows. We use two complementary approaches, one focusing on the size of total trade flows and one focusing on bilateral trade patterns (gravity equation). Besides, we control for two other domestic policy variables: trade policy and domestic infrastructure. We find that the quality of institutions has a positive and significant impact on a country's level of openness. Domestic tariffs have no statistically significant impact on their own, but do affect total trade flows when combined with good institutions. Domestic institutions also have a positive and significant impact on bilateral trade flows, but the parameter of our institution variables is reduced by almost a half and may turn insignificant when the quality of domestic infrastructure is included in the regression.
Keywords: F13; O19; O24; 330